The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2015
DOI: 10.1016/j.scog.2015.08.002
|View full text |Cite
|
Sign up to set email alerts
|

Increased Internet use and poorer ability to manage emotions in youth at high-risk for psychosis

Abstract: The relationship between Internet use and social behavior remains unknown. However, research indicates that Internet use (IU) may have some causal role in certain types of psychopathology and overall functioning. In contrast, other work suggests that IU may be protective and buffer against social isolation. Poorer emotional processing (EP) is characteristic of schizophrenia, and these deficits are present prior to illness onset (the ultra high-risk period (UHR)). UHR adolescents/young adults also fall within a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 49 publications
0
9
0
Order By: Relevance
“…These findings build on previous research arising from the SEYLE study which identified significant associations between pathological internet use and suicidal behaviours, depression, anxiety, conduct problems and hyperactivity/inattention (Kaess et al, 2014). The findings of the strong associations between maladaptive/pathological internet use and PEs in multivariate analysis adds to growing research which has identified a close link between pathological internet use and PEs (Mittal et al, 2013; Pelletier-Baldelli et al, 2015). It may be that the characteristics of individuals experiencing PEs render this group particularly susceptible to problematic internet use, in particular interpersonal deficits, social withdrawal or impulsivity (Mittal et al, 2013).…”
Section: Discussionmentioning
confidence: 52%
“…These findings build on previous research arising from the SEYLE study which identified significant associations between pathological internet use and suicidal behaviours, depression, anxiety, conduct problems and hyperactivity/inattention (Kaess et al, 2014). The findings of the strong associations between maladaptive/pathological internet use and PEs in multivariate analysis adds to growing research which has identified a close link between pathological internet use and PEs (Mittal et al, 2013; Pelletier-Baldelli et al, 2015). It may be that the characteristics of individuals experiencing PEs render this group particularly susceptible to problematic internet use, in particular interpersonal deficits, social withdrawal or impulsivity (Mittal et al, 2013).…”
Section: Discussionmentioning
confidence: 52%
“…Changes in the structure of emotional competence of young people when interacting with the Internet are also noted in the work [9], and the lack of elaboration of the problem is emphasized in the paper.…”
Section: Introductionmentioning
confidence: 95%
“…[6] emphasize the unpredictability of Internet activity and the opposition to upbringing and education as a result of virtual manipulation and digital destructive influence on young people with their unformed mental, psychological and social abilities. Most scientists, both Russian [5,6] and foreign [2,3,7,8,9] consider the uncontrolled Internet as a potential weapon of mass destruction, with the enormous power to transform a reasonable person with his or her value system in a very short period of time.…”
Section: Introductionmentioning
confidence: 99%
“…First, a developmentally-informed conceptualization of risk can be achieved by training clinicians on the unique developmental considerations of this age range, creating anchors within interview tools that reflect typical and atypical development, developing age-informed norms/cutoff scores, maintaining a sensitivity to response style biases, thoroughly probing endorsements to ensure a shared understanding of meaning, and committing to a longitudinal approach (clinically and through research). Second, investigators and clinicians alike can stay current on not only the literature (as we are regularly discovering new potential developmental confounds in this area), but also norms for adolescent behaviors [e.g., around social media use, social engagement patterns, and dating; (37, 38)] and recent trends in subculture identification and practice (a rapidly shifting area with many potential nuances that would likely confound accurate assessment and treatment). Further, investigators can be mindful not to treat the adolescent period as a unidimensional construct, but rather, understand that this is a dynamic span of time, beginning just at the end of late childhood and carrying many individuals into the mid to late 20's.…”
Section: Developmentmentioning
confidence: 99%